Computer Vision - ECCV 2020 Workshops Glasgow, UK, August 23-28, 2020, Proceedings, Part IV - Bartoli, Adrien; Fusiello, Andrea; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
The 6-volume set, comprising the LNCS books 12535 until 12540, constitutes the refereed proceedings of 28 out of the 45 workshops held at the 16th European Conference on Computer Vision, ECCV 2020. The conference was planned to take place in Glasgow, UK, during August 23-28, 2020, but changed to a virtual format due to the COVID-19 pandemic. The 249 full papers, 18 short papers, and 21 further contributions included in the workshop proceedings were carefully reviewed and selected from a total of 467 submissions. The papers deal with diverse computer vision topics. Part IV focusses on advances in image manipulation; assistive computer vision and robotics; and computer vision for UAVs.
W24 - Advances in Image Manipulation Workshop and Challenges -- DeepGIN: Deep Generative Inpainting Network for Extreme Image Inpainting -- AIM 2020 Challenge on Video Temporal Super-Resolution -- Enhanced Quadratic Video Interpolation -- AIM 2020 Challenge on Video Extreme Super-Resolution: Methods and Results -- Deformable Kernel Convolutional Network for Video Extreme Super-Resolution -- Multi-Objective Reinforced Evolution in Mobile Neural Architecture Search -- Deep Plug-and-Play Video Super-Resolution -- Deep Adaptive Inference Networks for Single Image Super-Resolution -- Densely Connecting Depth Maps for Monocular Depth Estimation -- Single image dehazing for a variety of haze scenarios using back projected pyramid network -- A Benchmark for Inpainting of Clothing Images with Irregular Holes -- Learning to improve image compression without changing the standard decoder -- Conditional Adversarial Camera Model Anonymization -- Disrupting Deepfakes: Adversarial Attacks AgainstConditional Image Translation Networks and Facial Manipulation Systems -- Efficiently Detecting Plausible Locations for Object Placement using Masked Convolutions -- L2-Constrained RemNet for Camera Model Identification and Image Manipulation Detection -- W25 - Assistive Computer Vision and Robotics -- We Learn Better Road Pothole Detection: from Attention Aggregation to Adversarial Domain Adaptation -- Multi-channel Transformers for Multi-articulatory Sign Language Translation -- Synthetic Convolutional Features for Improved Semantic Segmentation -- Autonomous Car Chasing -- SignSynth: Data-Driven Sign Language Video Generation -- ALET (Automated Labeling of Equipment and Tools): A Dataset for Tool Detection and Human Worker Safety Detection -- DMD: A Large-Scale Multi-Modal Driver Monitoring Dataset for Attention and Alertness Analysis -- Exploiting Scene-specific Features for Object Goal Navigation -- Active Crowd Analysis for Pandemic Risk Mitigation for Blind or Visually Impaired Persons -- Enhancing Robot-Assisted WEEE Disassembly through Optimizing Automated Detection of Small Components -- Structural Plan of Indoor Scenes with Personalized Preferences -- Behavioural pattern discovery from collections of egocentric photo-streams -- Motion Prediction for First-person Vision Multi-object Tracking -- i-Walk Intelligent Assessment System: Activity, Mobility, Intention, Communication -- Adaptive Virtual Reality Exergame for Individualized Rehabilitation for Persons with Spinal Cord Injury -- W26 - Computer Vision for UAVs Workshop and Challenge -- ATG-PVD: Ticketing Parking Violations on A Drone -- Next-Best View Policy for 3D Reconstruction -- A Flow Base Bi-path Network for Cross-scene Video Crowd Understanding in Aerial View -- Multi-view Convolutional Network for Crowd Counting in Drone-captured Images -- PAS Tracker: Position-, Appearance- and Size-aware Multi-Object Tracking in Drone Videos -- Insights on Evaluation of Camera Re-localization Using Relative Pose Regression -- A Deep Learning Filter for Visual Drone Single Object Tracking -- Object Detection Using Clustering Algorithm Adaptive Searching Regions in Aerial Images -- Real-Time Embedded Computer Vision on UAVs: UAVision2020 workshop summary -- VisDrone-CC2020: The Vision Meets Drone Crowd Counting Challenge Results -- VisDrone-DET2020: The Vision Meets Drone Object Detection in Image Challenge Result -- VisDrone-MOT2020: The Vision Meets Drone Multiple Object Tracking Challenge Results -- VisDrone-SOT2020: The Vision Meets Drone Single Object Tracking Challenge Results.
Keywords: Computer vision; Machine learning; Pattern recognition systems; Application software; Computers, Special purpose; Computer Vision; Machine Learning; Automated Pattern Recognition; Computer and Information Systems Applications; Special Purpose and Application-Based Systems